Optimization and control algorithm for calculating separating membranes pore shapes - Zhanat Umarova; Sevara D. Kurakbayeva; Aizhan T. Kalbayeva; Pernekul A. Kozhabekova; Zhalgasbek D. Iztayev; Nabat Suieuova (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This work was aimed at researching and developing a computer model, as well as an optimization and control algorithm for calculating pore shapes for separating membranes in separation processes. Two types of flow fluid rates through separation membranes with various pores configurations were considered. Here, the first type of pores had the form of a tortuous channel with sharp narrowing endings, which, in turn, could be assumed as “zero” wall thickness holes. The second type of pores had conical narrowing at the ends, which is closer to the real shape of the pores. As a result of the analysis of the performed calculations and models, data were obtained on the effect of the thickness of the selective layer on the performance of the membrane. In computer calculations, it was determined that the optimal volumetric porosity should be limited to 0.15, which affects the mechanical strength of the membrane. Calculations were also carried out on the Chemcad software product, which resulted in graphs of the optimal permeability of various liquids, depending on the differ curvature and pore volume of the separation membranes.